Study on the binding interaction of three-finger toxins from cobras and mangrove catsnake toward nicotinic acetylcholine receptors: a computational approach - Zulkifli, Nor Asyikin; Ahmad Rusmili, Muhamad Rusdi; Othman, Iekhsan; Ismail, Ahmad Khaldun; Chaisakul, Janeyuth; Ibrahim, Zalikha (IIUM Press, 2022)
Introduction: Snake venom is a combination of various proteins and peptides that cause diverse biological effects in multiple organ systems. Toxins from three-finger toxin family are the mains toxins in elapid venom. Although these toxins share similarities in their structure, they are known to cause a myriad of toxic actions such as neurotoxicity, cardiotoxicity, and cytotoxicity. Unfortunately, many of these toxins are not fully pharmacologically characterized, especially on their binding affinity and selectivity towards receptors and their effects to different organ systems.